Ocular Drug Delivery for Glaucoma Management - Barbara Wirostko; Balamurali K. Ambati; Bonnie Archer; Russell Condie; Randon Michael Burr; Sarah A. Molokhia; Nathan Gooch (Pharmaceutics, 2012)
Current glaucoma management modalities are hindered by low patient compliance and adherence. This can be due to highly complex treatment strategies or poor patient understanding. Treatments focus on the management or reduction of intraocular pressure. This is most commonly done through the use of daily topical eye drops. Unfortunately, despite effective therapies, glaucoma continues to progress, possibly due to patients not adhering to their treatments. In order to mitigate these patient compliance issues, many sustained release treatments are being researched and are entering the clinic. Conjunctival, subconjunctival, and intravitreal inserts, punctal plugs, and drug depots are currently in clinical development. Each delivery system has hurdles, yet shows promise and could potentially mitigate the current problems associated with poor patient compliance.